Współczesne tendencje rozwoju wymiany towarowej między Japonią i Chinami - Pasierbiak, Paweł (Contemporary tendencies in trade development between Japan and China, 2009)
The author of the article analyzes trade development in goods between Japan and China since 2000. The main tendencies were identified: a dynamic growth of trade in value terms, a continuous Japanese trade deficit with China and an improvement in a commodity structure of Chinese exports to Japan. The main factors of trade development were also indicated. These were: an economic conjuncture in the world economy, in China and Japan; partners’ trade policies and direct investments in China by Japanese TNCs. A current trend in trade development was reversed at the end of 2008, when mutual exports and imports started to show a regression. The most serious economic slowdown since the Second World War makes the prospects of trade between Japan and China gloomy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 249-261